Endogenous opiate analgesia induced by tonic immobility in guinea pigs - Leite-Panissi,C.R.A. (2001)
A function of the endogenous analgesic system is to prevent recuperative behaviors generated by tissue damage, thus preventing the emission of species-specific defensive behaviors. Activation of intrinsic nociception is fundamental for the maintenance of the behavioral strategy adopted. Tonic immobility (TI) is an inborn defensive behavior characterized by a temporary state of profound and reversible motor inhibition elicited by some forms of physical restraint. We studied the effect of TI behavior on nociception produced by the formalin and hot-plate tests in guinea pigs. The induction of TI produced a significant decrease in the number of flinches (18 ± 6 and 2 ± 1 in phases 1 and 2) and lickings (6 ± 2 and 1 ± 1 in phases 1 and 2) in the formalin test when compared with control (75 ± 13 and 22 ± 6 flinches in phases 1 and 2; 28 ± 7 and 17 ± 7 lickings in phases 1 and 2). In the hot-plate test our results also showed antinociceptive effects of TI, with an increase in the index of analgesia 30 and 45 min after the induction of TI (0.67 ± 0.1 and 0.53 ± 0.13, respectively) when compared with control (-0.10 ± 0.08 at 30 min and -0.09 ± 0.09 at 45 min). These effects were reversed by pretreatment with naloxone (1 mg/kg, ip), suggesting that the hypoalgesia observed after induction of TI behavior, as evaluated by the algesimetric formalin and hot-plate tests, is due to activation of endogenous analgesic mechanisms involving opioid synapses.